Collaborative data acquisition and processing for post disaster management and surveillance related tasks using UAV-based IoT cloud. (9th July 2020) - Kumar, J. Sathish; Kumar, Saurabh; Choksi, Meghavi; Zaveri, Mukesh A.
Rescue and recovery operations are very critical for post disaster management. For post disaster management and surveillance activities, there is a need of acquiring the information about the ground situation through sensing or observing data and identify the locations, which is a challenging task. These data may be sensed or observed through different types of sensors deployed in the area of interest. This can be achieved through a collaborative way of data acquisition and processing. In this context, this paper introduces the framework for data acquisition based on collaborative processing using unmanned aerial vehicles and internet of things network. The major contribution of this work is that the real time test bed using actual UAVs and IoT devices for data acquisition, clustering of different sensors and devices deployed for it and localising the sensors and different events or situations arising in the region of interest is detailed and demonstrated. The framework is evaluated using real test bed with drones (UAVs) and integrated with cloud platform in IoT-based environment for data storage of the acquired data for further analysis and effective decision making in disaster situations.